Incipient Games: Restoring the Past Through Play in Historical Reenactment - (:unkn) unknown (My University, 2022)
This thesis is an ethnography of an historical reenactment group which stewards a living history village portraying the nineteenth-century “Wisconsin frontier.” It analyzes productions from improvisations, to scripted vignettes, to a “whodunit” mystery game. Across their practice, reenactors are met with a host of challenges including ‘authenticity,’ balancing constructionism and objectivism, visitor engagement, educating the public, and the bleeding together of period techniques and modern thinking. Such challenges push against the boundaries of analyzing the project of reenactment (or larger social life) as theatre. Given terms like “play-acting” and “role-playing” in the space of reenactment, this thesis examines this phenomenon employing Richard Schechner’s theatrical notion of “restored behavior.” It applies restored behavior to extend the arc from ritual to theatre to arrive at ‘incipient’ games: the notion that the cultural product emerges in the ‘taking up’ of play. It concludes that games are needed to make something of reenactment beyond theatre.
Keywords: Ethnography; Games; Historical Reenactment; Performance; Play; Wisconsin